1997
DOI: 10.1099/0022-1317-78-10-2467
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of persistent hepatitis C virus infection and replication in vitro.

Abstract: Hepatitis C virus (HCV) is a major cause of chronic viral hepatitis. Development of anti-viral strategies has been hampered by the lack of efficient cell systems to propagate HCV in vitro. To establish a long-term culture system, we tested human hepatoma (HuH7, HepG2) and porcine non-hepatoma (PK15, STE) cell lines, as well as several culture and infection conditions. As a marker for virus replication, minus-strand HCV RNA in infected cells was detected by an enhanced detection system using nested RT-PCR follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 50 publications
9
68
0
1
Order By: Relevance
“…The susceptibility of HepG2 cells to HCV infection and its support for viral replication agree with previous reports [19,21,25]. The sensitivity of human anti-HCV-antibody positive sera to detect HCV antigens in infected HepG2 agrees with the observations of El-Awady et al [21].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The susceptibility of HepG2 cells to HCV infection and its support for viral replication agree with previous reports [19,21,25]. The sensitivity of human anti-HCV-antibody positive sera to detect HCV antigens in infected HepG2 agrees with the observations of El-Awady et al [21].…”
Section: Discussionsupporting
confidence: 82%
“…Infection of HepG2 cells was performed according to protocols described previously with some modifications [19,25]. In 12-well plates, cells were grown for 24 hours to semi-confluence in complete medium, washed three times with FBS-free medium then inoculated with sterile filtered HCVinfected serum through a 0.22 µm syringe filter to a final concentration of 10%.…”
Section: Infection Of Hepg2 Cells With Hcvmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Furthermore, continued stimulation of LDLR expression enhanced virus replication in vitro. 39 The serum concentration of beta-lipoproteins is thought to influence HCV concentration, as the former could inhibit the binding of the virus to its proposed receptor, the LDLR. Indeed, it was demonstrated that beta-lipoproteins negatively affected the level of HCV-Ag.…”
Section: Discussionmentioning
confidence: 99%
“…To date, HCV has been shown to replicate in vitro in human lymphocytes (Cribier et al, 1995 ;Kato et al, 1995 ;Mizutani et al, 1996 b ;Shimizu et al, 1992Shimizu et al, , 1993Shimizu & Yoshikura, 1994), human fibroblasts (Zibert et al, 1995), chimpanzee hepatocytes (Lanford et al, 1994) and human hepatocytes (Ikeda et al, 1997(Ikeda et al, , 1998Ito et al, 1996 ;Seipp et al, 1997). Evidence that HCV possesses cell tropism come from the findings that an HCV population with a limited hypervariable region 1 (HVR1) sequence, which is located in the N-terminal region of the second envelope glycoprotein (E2) (Hijikata et al, 1991 b ;Weiner et al, 1991), became predominant in cultured cells, despite the complicated quasispecies of the HVR1 in the primary inoculum (Hijikata et al, 1995 ;Ikeda et al, 1997 ;Kato et al, 1995 ;Nakajima et al, 1996 ;Sugiyama et al, 1997 b).…”
Section: Introductionmentioning
confidence: 99%